The interactions of model cationic drug with newly synthesized starch derivatives - Justyna Kobryń; Tomasz Zięba; Magdalena Rzepczyńska; Witold Musial (International Association of Physical Chemists (IAPC), 2023)
Background and purpose: The aim of the work was to compare the interactions of three newly synthesized non-toxic starch derivatives, with varied anionic and non-ionic functional groups with methylene blue (MB) as a model cationic drug, and selection of starch derivative with highest affinity to the MB. Experimental approach: The native potato starch (SN), modified via acetylation (SM1), esterification and crosslinking (SM2) and crosslinking (SM3), was evaluated in MB adsorption studies and assessed by FTIR, PXRD, and DSC. Key results: The adsorption of MB on SM2 and SM3 matched the BET isotherm model, which confirmed physisorption on the low-porous surface. In the case of SM1, adsorption took place via electrostatic attraction between the heterogeneous adsorbent surface and the adsorbate, as demonstrated by the Freundlich plot. The FTIR confirmed vibrations assigned to N=C stretching bonds at 1600 cm-1 in the case of MB adsorbed on the SN and SM2. The most intense PXRD peaks belonged to SN and the least to SM2. In the DSC study, the thermal stability via ΔT was assessed, with SM2 of lowest ΔT value (179.8 °C). Conclusion: SM2 presented the best adsorption capacity, followed by SM3 and the weakest SM1. The interactions were confirmed in the adsorption studies and may reflect applications of the modified starches as drug carriers. In the FTIR study, a probable interaction between the OH- groups of SM2 and N+ of MB was revealed. The most amorphous structure was shown for SM2, which was correlated with the lowest thermal stability provided by the DSC study.